2021
DOI: 10.1200/op.20.00395
|View full text |Cite
|
Sign up to set email alerts
|

Comanagement Strategy Between Academic Institutions and Community Practices to Reduce Induction Mortality in Acute Promyelocytic Leukemia

Abstract: PURPOSE: Acute promyelocytic leukemia (APL) is a curable leukemia with > 90% survival in clinical trials. Population-based studies from Sweden and US SEER data have shown long-term survival rates of 62% and 65.7%, with the lower rate being from a higher percentage of early deaths. METHODS: In this prospective, multicenter trial, we developed a simplified algorithm that focused on prevention and early treatment of the three main causes of death: bleeding, differentiation syndrome, and infection. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Recent evidence has shown that a comanagement strategy between academic institutions and community practice may lower EDs to ,10%. 51 Because APL is rare, centralized expertise, with experience in providing supporting care and managing complications, is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that a comanagement strategy between academic institutions and community practice may lower EDs to ,10%. 51 Because APL is rare, centralized expertise, with experience in providing supporting care and managing complications, is essential.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the early mortality in APL, Jillella et al designed a prospective multicenter clinical trial facilitating APL comanagement strategy between academic institutions and community oncology practices [ 23 ]. This approach allowed use of remote consultancy between APL experts and community oncologists treating patients with APL.…”
Section: Approach To Suspected Aplmentioning
confidence: 99%
“…Further, the outcomes of patients in clinical trials and population-based registry studies vary substantially. 4,5,[8][9][10][11][12] The factors underlying these survival differences are unknown. Prior studies have suggested survival differences based on patient demographics (age, race and socioeconomic status) and treatment setting, with more favorable outcomes observed for patients treated at academic or National Cancer Institute designated cancer centers.…”
Section: Introductionmentioning
confidence: 99%